Power and accountability – Using Biblical lenses to explore contemporary challenges in Africa - Mwandayi, Canisius (HTS teologiese studies, 2023)
The Bible is one of the most influential documents in human history that has not only changed believers’ lives but has also greatly influenced our society whether one is a Christian or not. While the Western world has somehow managed to remove the Bible from the public sphere and religion relegated as the opium of the oppressed masses in the Communist bloc, to Africans, the Bible has remained a moral compass without which human life becomes ungovernable. As the Bible has come to occupy such a high place of authority in African life, the aim of this article is to examine the contemporary challenges that Africa is facing concerning issues of power and accountability in light of selected biblical texts. Using largely the canonical approach and socio-cultural anthropology, this article takes the Bible as a mirror that leaders should use to self-introspect in regard to their exercise of power and accountability to their subjects. It is our observation that there is now a tendency among African leadership especially during elections to rush to claim vox populi, vox Dei meaning ‘the voice of people is the voice of God’, yet rigging and failure to live up to God’s dictates may be manifestly characterising one’s leadership. A fish begins rotting in its head hence it is our conclusion that it is only by having a leadership that cultivates a fear of God at its heart that Africa can be healed of its problems.Contribution: In Africa, it is a paradox that while some political leaders purport to have been schooled in the Bible in mission schools, they lead a life divorced from it. This article adds a voice to the on-going religion and politics dialogue in Zimbabwe by soliciting an honest adherence to its principles.